IMPLEMENTATION OF THE BOLOGNA PROCESS IN PORTUGAL - David, Fátima (2009)
Concerning to the current diversification of the Higher Education, which goes through the scientific and technical progress and the individual interests and social needs of qualified personnel, this research discusses the new paradigm of Higher Education in Portugal, as consequence of Bologna Process, and in the context of the Superior School of Technology and Management (SSTM) of Guarda, as a case study of this evidence. In a society based on the intensive knowledge use, the expectations on the qualifications level and competences has grown considerably, carrying out the formation, in general, and the one of superior level, in particular, a strategic function. In fact, the sustainable social, economical and technological development demands a constant (re)adaptation of the conceptual field and as a consequence, of the general knowledge as well as the technical skills and competences, which should be insured by the Higher Education once it is a dynamic process, in which qualifications and competences have the risk of fast obsolescence.